« Mourir effectivement au monde » : l’écriture spirituelle de Jacqueline pascal entre mortification et renouvellement intérieur - Giada Silenzi (Noctua, 2025)
This article examines the spiritual journey of Jacqueline Pascal, focusing on the central role that writing played in her religious vocation. It follows her progression from a celebrated poet in Parisian literary circles to her eventual commitment to the religious life at Port-Royal, where she embraced humility and simplicity under the guidance of Mother Agnès Arnauld. Central to this transformation is her reappropriation of language, which she turned into an instrument of inner purification, drawing on biblical models and Augustinian principles that shaped contemplative life at Port-Royal. The analysis of her meditation on the mystery of Christ’s death demonstrates how Jacqueline Pascal’s writing became an active spiritual practice, illustrating her stylistic shift from her earlier worldly poetry to a meditative and austere prose. Through the use of rhetorical devices such as repetition, her writing embodies the inner struggle for self-discipline and spiritual renewal, reflecting her commitment to her future religious life at Port-Royal.